Structural and functional changes of the heart in chronic heart failure with preserved left ventricular ejection fraction with excess body weight depending on the presence and form of atrial fibrillation - Bidzilya, P. P.; Kadzharian, V. H. (Zaporozhye Medical Journal, 2021)
The aim. To examine the features of structural and functional changes of the heart in patients with chronic heart failure with preserved left ventricular ejection fraction (CHF pr EF) with excess body weight depending on the presence and form of atrial fibrillation (AF). Materials and methods. The study involved 248 patients with CHF pr EF and excess body weight, the mean age was 65.0 ± 11.0 years, 146 females (58.9 %) and 102 males (41.1 %). The first group included 181 patients without concomitant AF, the mean age was 64.0 ± 11.0 years, 110 females (60.8 %) and 71 males (39.2 %); the second group included 67 patients with AF, the mean age was 67.9 ± 11.3 years, 36 females (53.7 %) and 31 males (46.3 %). Subjects with AF were further divided into subgroups: 7 patients with paroxysmal AF, the mean age – 6.7 ± 10.4 years, 3 females (42.9 %) and 4 males (57.1 %), 12 patients with persistent AF, the mean age – 70.8 ± 10.3 years, 10 females (83.3 %) and 2 males (16.7 %); 48 patients with permanent AF, the mean age – 67.3 ± 11.7 years, 23 females (47.9 %) and 25 males (52.1 %). Results. Patients with concomitant AF had a significantly larger aorta diameter (by 3.0 %), systolic left atrium size (LAs) (by 14.5 %), right atrium size (RA) (by 8.3 %), left ventricle end-diastolic size (LVEDS) (by 7.1 %), left ventricle end-systolic size (LVESS) (by 10.6 %), right ventricle size (RV) (by 13,1 %), mean pulmonary artery pressure (by 20.0 %) and the prevalence of LV eccentric hypertrophy (by 21.0 %; P ˂ 0.001). At the same time, LV wall relative thickness (LV RT) was lower by 6.3 %, LV EF – by 3.4 % and the frequency of LV concentric hypertrophy – by 19.1 % (P ˂ 0.001). In permanent form of AF compared to paroxysmal one, significantly larger LAs (by 10.6 %), RA (by 10.9 %), LV myocardial mass (LV MM) (by 18.1 %) and LV MM index (by 21.1 %) were determined and in contrast to persistent AF, LAs (by 9.8 %), RA (by 11.4 %), LVEDS (by 15.6 %), LVESS (by 15.8 %), RV (by 27, 9 %), LV MM (by 29.8 %), LV MMI (by 14.9 %) were predominant, at the same, LVRT was 12.8 % less. Conclusions. In patients with CHF pr EF and excess body weight, concomitant AF is associated with greater dilatation of the heart cavities, eccentric hypertrophy predominance, decreased LV contractility and pulmonary hypertension. Compared to other forms, permanent AF is characterized by severe structural and functional changes in the heart, maximal manifestations of LV dilatation and hypertrophy.